2004
DOI: 10.1289/ehp.7161
|View full text |Cite
|
Sign up to set email alerts
|

Production of Androgens by Microbial Transformation of Progesterone in Vitro : A Model for Androgen Production in Rivers Receiving Paper Mill Effluent

Abstract: We have previously documented the presence of progesterone and androstenedione in the water column and bottom sediments of the Fenholloway River, Taylor County, Florida. This river receives paper mill effluent and contains masculinized female mosquitofish. We hypothesized that plant sterols (e.g., β-sitosterol) derived from the pulping of pine trees are transformed by bacteria into progesterone and subsequently into 17α-hydroxyprogesterone, androstenedione, and other androgens. In this study, we demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 23 publications
4
46
0
2
Order By: Relevance
“…The biotransformation of the first two pathways happened at 17β position at ring-D. Progesterone was transformed via the first pathway into 17α-hydroxyproges- terone (17α-OHP), and subsequently into AED and ADD. This could be supported by the previous study of Jenkins et al, 38 who found the same transformation by bacteria. Based on previous studies about steroids biodegradation, 21,25,27,38,39 progesterone could be transformed into testosterone acetate (TAC) and four identified products (1−4) T, 17β-BOL, AED, and ADD via the second pathway, where these products could be converted to one another (Figure 4).…”
Section: ■ Results and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The biotransformation of the first two pathways happened at 17β position at ring-D. Progesterone was transformed via the first pathway into 17α-hydroxyproges- terone (17α-OHP), and subsequently into AED and ADD. This could be supported by the previous study of Jenkins et al, 38 who found the same transformation by bacteria. Based on previous studies about steroids biodegradation, 21,25,27,38,39 progesterone could be transformed into testosterone acetate (TAC) and four identified products (1−4) T, 17β-BOL, AED, and ADD via the second pathway, where these products could be converted to one another (Figure 4).…”
Section: ■ Results and Discussionsupporting
confidence: 83%
“…This could be supported by the previous study of Jenkins et al, 38 who found the same transformation by bacteria. Based on previous studies about steroids biodegradation, 21,25,27,38,39 progesterone could be transformed into testosterone acetate (TAC) and four identified products (1−4) T, 17β-BOL, AED, and ADD via the second pathway, where these products could be converted to one another (Figure 4). Compared with the residual progesterone in the media, the concentrations of these four detected steroids (products 1−4) by LC-MS/MS, 16 were very low (below 14 μg/L), reaching a peak at 5.7 h, then decreasing gradually (SI Figure S6), indicating that only a relatively low percentage of progesterone was degraded into these androgens, where they were also easily degraded under aerobic conditions.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
“…Surface water and sediment samples were collected from the Liuxi, Shijing, and Zhujiang rivers of the Pearl River system in the dry season (December [17][18]2007) and the wet season (September [10][11][12]2008). In total, 15 sampling sites along the three rivers were selected (Fig.…”
Section: Sample Collection and Extractionmentioning
confidence: 99%
“…Male fish feminization in receiving waters has been related to residual natural and synthetic estrogens from municipal STP effluents [8,9]. Effluents from pulp and paper mills displayed androgenic activity in female fish, leading to masculinization or sex reversal of female fish [10,11]. Very recently, screening assays revealed that androgenic activity also exists widely in industrial and hospital wastewaters, municipal STP effluents, and even in surface water in association with estrogen, progesterone, and glucocorticoid receptor activities [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the androgenic and antiandrogenic activities of chemicals have been described in association with paper and pulp mill effluents (Svenson and Allard, 2004), rivers (Thomas et al, 2002), and effluents from wastewater treatment plants (Blankvoort et al, 2005). While androgenic activity in rivers may be a partial result of microbial degradation of phytosterols to progesterone and then to androgens (Jenkins et al, 2004), anti-androgenic activity is derived from anthropogenic chemicals (Sumpter, 2005). Naturally occurring reproductive hormones such as 17b-estradiol, testosterone, and their metabolites are commonly detected in sewage treatment works (STW) effluents (Desbrow et al, 1998).…”
Section: Introductionmentioning
confidence: 99%